EFFECT OF PROFITABILITY, LEVERAGE, AND COMPANY SIZE ON TAX AVOIDANCE IN PLANTATION SECTOR COMPANIES - Fida Oktafiani,; Rahmat Putra Ahmad Hasibuan,; Riata Dheasita Safira,; Muhammad Rinaldi,; Jenni Veronika Br Ginting, (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to analyze effect of profitability, leverage, and company size on tax avoidance in Plantation Sector Companies. This type of research is causal research with a quantitative approach. The type of data to be collected is secondary data in the form of quantitative data. The research data is obtained from information available on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. This quantitative data is in the form of company financial reports, starting from 2018 to 2022. Sampling in this study is carried out using the census method, in which the entire target population is sampled. So the number of samples in this study are 14 companies. Testing the hypothesis in this study uses the estimation results of fixed effect model regression. The results show that profitability has a positive and significant effect on tax avoidance in Plantation Sector Companies. Leverage has a negative and significant effect on tax avoidance in Plantation Sector Companies. Company size has a positive and not significant effect on tax avoidance in Plantation Sector Companies.